Tree growth and inner characteristics of fruits in pear cultivars - Iváncsics, J.; Vadas, Z.; Jekkel, G. (International Journal of Horticultural Science, 2005)
Summary The aim of study was to investigate growth (crown growth and trunk diameter) and fruit characteristics [dry matter content (%), pectin (%), total acid (%) contents] of 10 pear cultivars (’Móri császár’, ’Nyári Kálmán’, ’Mogyoródi óriás’, ’Fehérvári körte’, ’Szegfa körte’, ’Piroska’, ’Mézes körte’). The crown development of the cv. ’Fehérvári körte’ can be regarded as outstanding among the examined cultivars. The growth of the cv. ’Mogyoródi óriás’ was low, this cultivar showed the poorest growth vigour. The width of the crown in several cultivars developed at a similar rate as the height of the crown. Outstanding values were shown by cvs. ’Fehervári körte’ and ’Móri császár’. The development of trunk diameter was the highest for cvs. ’Piroska’ and ’Hóka’, and large growth of trunk diameter can be seen on cv. ’Fehervári körte’. Cvs. ’Mogyoródi óriás’ and ’Mezes körte’showed weak growth. Outstanding dry matter content of fruits was measured on cvs. ’Fehervári körte’ and ’Mézes körte’. The total acid content of fruits of cvs. ’Mézes körte’ and ’Fehérvári körte’’ was significantly different from the total acid content of cv. ’Mogyoródi óriás’. Pectin content was low in fruits of cvs. ’Mogyoródi óriás’ and ’Fehérvári körte’, while cv. ’Mézes körte’ contained significantly more pectin. Vitamin C content we found was rather high in cvs. ’Mézes körte’ and ’Fehérvári körte’.